The mental health of mothers and fathers during pregnancy and early parenthood after successful oocyte donation treatment: A nested case‐control study. (6th August 2018) - Sälevaara, Mari; Punamäki, Raija‐Leena; Unkila‐Kallio, Leila; Vänskä, Mervi; Tulppala, Maija; Tiitinen, Aila
Abstract: Introduction: The aim of this study was to compare the mental health problems between parents after oocyte donation treatment, after in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) with own gametes and after naturally conceiving (NC). Material and methods: This is a prospective, longitudinal questionnaire study. The study group consisted of 26 oocyte donation mothers and their matched IVF/ICSI (n = 52) and NC (n = 52) controls. Matching was performed according to mother's age, parity, type of pregnancy, and number of returned questionnaires. The parents filled‐in the General Health Questionnaire (GHQ‐36) at gestational weeks 18‐20 (T1), and at 2 months (T2) and 12 months (T3) after the childbirth. Results: Full response rate (T1‐T3) for oocyte donation mothers was 76.9% and for oocyte donation fathers was 73.1%. At T1, no significant differences were found between groups in depression, anxiety, sleeping difficulties, or social dysfunction, but they differed at T2 and T3 in anxiety (T2, P  =   .02; T3, P  =   .01), in sleeping difficulties (T2, P  =   .02; T3, P  =   .04) and in social dysfunction (T2, P  =   .01; T3, P  =   .04). Oocyte donation mothers showed less anxiety than NC mothers (T2, T3), and fewer sleeping difficulties and less social dysfunction than IVF/ICSI (T2, T3) and NC mothers (T2). Mental health problems of oocyte donation fathers did not differ from those of IVF/ICSI and NC control fathers at T1‐T3. Conclusions: Oocyte donation mothers showed fewer mental health symptoms in early parenthood compared with IVF/ICSI and NC mothers. No differences were found among mothers during pregnancy and among fathers at any time point.